IoT-Project Smart Trash Can with Blynk Platform Integration - Noffal Ade Putra; Hero Akbar Ahmadi; Kielvien Lourensius Eka Setia Putra; Alexander AS Gunawan (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
This research is an implementation of the internet of things (IoT) for smart trash cans in places that are usually visited by many people. Currently, the Covid-19 pandemic in Indonesia is still quite high. Therefore, the Internet of Things (IoT) system is intended to help reduce the spread of the covid-19 virus. This system uses a NodeMCU ESP8266 microcontroller and several sensors that are used to support this research. The design of this IoT system focuses on measuring the distance between the trash can and the person disposing of the trash to calculate the opening and closing distance for the trash and measuring the height of the trash in the trash as a reference for cleaning workers to pick up trash at the right time. This smart trash can can open the lid automatically according to a specified distance and will send an alarm to the cleaning worker smartphone on duty when the height of the trash is full or reaches a predetermined limit.Keywords: Internet of Things, Covid-19, Smart Trash Can, Blynk Platform